Perancangan Sistem Informasi Berita Acara dan Sertifikasi Penerimaan Limbah B3 Pada PT Omega Cipta Kencana - Asworowati, Ratih Dwi; Mustomi, Dede; Natong, Asriani; Azizah, Ayu; Ulum, Khoirul; Wijaya, Dede Aldi (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The official report and certificates of receipt of b3 waste are a single document that must be issued by the waste transporter and collector to be submitted to the waste generating party, when the transporter has transported and placed the waste at a temporary b3 waste collection site. PT. Omega Cipta Kencana, which acts as a transporting party as well as a temporary b3 waste collection site, is required to issue an official report and certificate and hand them over to the party producing the waste. The purpose of making an official report and certificate of B3 waste is to find out that the waste has been received and placed in a temporary B3 waste collection site according to the permits owned, and as a condition for completing company documents as really needed when the company comes for an audit. The method of collecting data in the preparation of the Final Project is the method of observation, interviews and literature study. With the creation of an information system for official reports and certification of acceptance of b3 waste, PT. Omega Cipta Kencana, which acts as the transporting party and as a temporary waste collection site, can issue these documents to the waste generator quickly, precisely and accurately and can save costs in the document delivery process. You can also store these documents safely and neatly in the system.